Material hardship and 529 college savings plan participation: the mitigating effects of Child Development Accounts - Wikoff, Nora; Huang, Jin; Kim, Youngmi; Sherraden, Michael (Elsevier, 2015)
Experience of material hardship can adversely affect a family’s ability to make long-term investments in children’s development. We examine whether material hardship is associated with one indicator of such investments: participation in a tax-advantaged college savings plan (529 plan). Data for this study come from the SEED for Oklahoma Kids (SEED OK) experiment, an intervention that offers Child Development Accounts with financial incentives to encourage the accumulation of college savings for children from the time of their birth. Results show that material hardship is negatively associated with 529-plan participation, and this association varies by treatment status. At all levels of material hardship, treatment-group mothers are more likely to hold accounts than control-group mothers. These findings suggest that CDAs can be a useful policy tool to support families’ financial preparation for college.